Modeling the potential public health and economic impact and cost-effectiveness of vaccination strategies using an adapted COVID-19 vaccine in Mexico - Carlos Fernando Mendoza; Jose Luis Huerta; Iustina Chirila; Dania Abreu; Moe H. Kyaw; Benjamin Yarnoff (Expert Review of Vaccines)
Background This study evaluated the impact of vaccination strategies using an adapted COVID-19 vaccine in Mexico.Research design and methods This study used a previously published combined Markov-decision tree model adapted for the Mexican context. The base case examined the population aged ≥ 65 years and the high-risk population (defined as those with one or more comorbidities associated with high risk of severe disease) aged 12–64 years. Scenario analyses examined lower age cutoffs for eligibility in the standard risk population (≥50 years, ≥18 years, and ≥12 years). Sensitivity analyses varying the parameters by ± 20% was conducted to assess uncertainty.Results Compared to no vaccination, the base case was estimated to prevent 1,509,194 cases, 132,166 hospitalizations 24,575 deaths, and 276,223 lost quality-adjusted life-years (QALYs), increasing direct costs by $602,446,820 and decreasing societal cost by $2,264,266,271. The ICER was dominant from the societal perspective and $2,181 from the payer perspective, which was cost-effective at a willingness-to-pay threshold of 1× GDP per capita ($11,812). The benefits were further increased in scenarios expanding vaccination to additional age groups.Conclusions Vaccination strategies targeting a broader age range with an adapted vaccine would result in considerable health and economic benefits and be cost-effective in Mexico.